URGENSI PENYELESAIAN SENGKETA WANPRESTASI - Reza Al Fajar; Ashar Sinilele (Alauddin Law Development Journal)
This study aims to find out what factors led to the occurrence of defaults of BRI bank customers in Bulukumba District and the consideration of Judges of the BulukumbaDistrict Court regarding the case of BRI bank customer defaults in Bulukumba Regency. This type of research is field research in the Bulukumba District Court by processing data on the results of trials that occur from 2017 to 2019. The sources of premier data and secondary data sources. Data collection methods obtained using the method of observation to the court and documentation, while data processing techniques use the process of comparing cases from year to year. The results showed that in a span of three years there were only 63 cases of defaults that were tried in the Bulukumba district court and the results of the decisions were minutations. Of the 63 cases there were only 8 cases which were not breaches of the BRI bank. Bulukumba regency is still relatively stable so that the case of bank loans that cause defaults is still lacking.